Modelling Business Sector Supply for the Smaller OECD Countries - Torres, Raymond (OECD Publishing, 1989)
This paper presents business sector supply blocks for thirteen smaller OECD economies. The starting point is the approach adopted by the Economics and Statistics Department for the major economies. The structure of the supply blocks is explained and estimation results are presented. Results from several diagnostic simulations using the new blocks are also presented. Finally the way the supply blocks can be used to compare aggregate supply and demand is set out ...
Keywords: Economics